Grande mídia e a construção de uma legitimidade discursiva sobre a universidade brasileira durante a greve de 2015 - Santos, Maria Stella Galvão (2018)
This research was developed about “Great media and the construction of a discursive legitimacy in 2015 brazilian public university strike". The research aimed to analyze the tension between two sides, the university and the media. Its goal was to analyze the discursive production of the mass media on the Brazilian public university, based on the news published during the teachers‟ and employees‟ 2015 strike, in order to find strategies both sides, university leaders and strikers had adopted to defend their points of view. These positions show distinct social groups‟ process to build a discursive hegemony in the discourse building during the studied period. The theoretical framework was based on Pierre Bourdieu's Reflective Sociology, notably on their concepts of symbolic power and of journalism as an homogenizing content of social fields, and on the production mechanisms for the selective construction of opinions and representations about social reality. The concepts of social field and habitus present in Bourdieu's work were used in order to clarify structural aspects of the dynamics of the press in Brazilian society and its relationship with the academic, economic and political fields. The theoretical framework also includes authors such van Dijk, Fairclough and Fowler, who, as Bourdieu (although with distinct formulations) help clarify and expose news practices that allowed them to create a hegemonic sense about the university during 2015 strike, in socio-political-economic context. To analyze raw data, we used key communication theory concepts, such gatekeeping, agenda-setting and 'news values'. These concepts were closely linked to the selection of events and criteria of relevance for news reporting. The methodology adopted was based on the assumptions of Critical Discourse Analysis, a conceptual and pragmatic tool developed by the aforementioned authors, which allowed identifying, between May and October 2015, both the news production strategies and the construction of the (Folha de S. Paulo, O Estado de S. Paulo and Correio Braziliense) and a news portal (G1, from Grupo Globo). The results reveal not only the filters that permeate the process of news production, such as the rarefied reports about the movement, the coverage limited to the superficiality of the facts or the priority of placement in the decline of the movement, as well as the different discursive strategies supported, for example, in the manipulation of titles that deviate from the content of the news or in the selection of interviewees whose statements sought to legitimize a given vision about the movement surveyed and public higher education in the country.